Comparative Evaluation of Calcium Chloride and Polyethylene Glycol 400 on Drug Loading in Human Plasma-Derived Exosomes: Insights from BCS class II drug Spironolactone - Laraib Khan; Rabia Gul; Muhammad Sarfraz; Hamid Bashir; Nabi Shah; Nadeem Ahmad; Hafiz Rashid Hussain; Sabeeh Mohsin; Izna Khan; Yasser Shahzad; Imran Nazir; Muhammad Imran Amirzada (Journal of Pharmaceutical Innovation, 2027)

Polymeric Based Bioinspired Microneedle Patch for the Treatment of Androgenetic Alopecia (AGA) - Muhammad Irfan Siddique; Shaher Bano; Muhammad Sarfraz; Arslan Ghazanfar; Talha Jawaid; Tahir Ali Chohan; Muhammad Naeem; Abida Khan (Journal of Pharmaceutical Innovation, 2026)

Slope gradients mediate the effects of newly returned crop residues on soil nutrient dynamics and microbial diversity in Mollisol maize monoculture systems in Northeast China - Anwar Zeb; Liang-Jun Hu; Xu Li; Gohar Ali; Atteqa Akbar; Sarfraz Ahmed; Muhammad Awais Haider; Amrozia Naz (Agriculture, Ecosystems & Environment, 2026)

Development and Characterization of Exosomes Mediated Transdermal Gel for Enhanced Delivery of Hydroxyurea - Wajeeha Khalid; Rabia Gul; Muhammad Sarfraz; Hamid Bashir; Nadeem Ahmad; Nayab Tahir; Aneela Javed; Muhammad Asad; Ahsan Ibrahim; Aamra Imtiaz; Imran Nazir; Muhammad Imran Amirzada (Journal of Pharmaceutical Innovation, 2026)

Retraction notice to ‘Hispolon: A natural polyphenol and emerging cancer killer by multiple cellular signaling pathways’ [Environ. Res. 190 (2020) 110017] - Ayesha Sarfraz; Azhar Rasul; Iqra Sarfraz; Muhammad Ajmal Shah; Ghulam Hussain; Nusrat Shafiq; Muqaddas Masood; Şevki Adem; Satyajit D. Sarker; Xiaomeng Li (Environmental Research, 2026)

Integrated probabilistic seismic hazard and risk assessment of Hunza District, northern Pakistan - Muhammad Waseem; Muhammad Shafique; Waqas Ahmed; Sarfraz Khan (Bulletin of Earthquake Engineering, 2026)

Spatiotemporal Distribution of Cyanobacteria in Tropical Freshwater Reservoir and Machine Learning Prediction using Explainable Artificial Intelligence - Muhammad Sarfraz Ahmad Mangat; Teh Sabariah binti Abd Manan; Sharifah Sakinah Syed Abd Mutalib; Zarimah Mohd Hanafiah; Nur Azwa Muhamad Bashar; Salmia Beddu; Nur Liyana Mohd Kamal; Daud Mohamad; Shatha Aser Hamad Aldala’in; Adel Gohari; Wan Hanna Melini Wan Mohtar; Muhammad Raza Ul Mustafa; et al. (Water, Air, & Soil Pollution, 2026)

Physiologically based pharmacokinetic modeling of cefotaxime to inform pediatric dosing in renal impairment - Najia Rahim; Muhammad Sarfraz; Muhammad Wahajuddin (European Journal of Clinical Pharmacology, 2026)
Background Cefotaxime (CFT) is a broad spectrum, third-generation cephalosporin antibiotic prescribed for the treatment of severe infections, yet dosing guidelines for pediatric with renal impairment is scarce. The current study aimed to develop a physiological based pharmacokinetic (PBPK) model to characterize CFT disposition and model-based recommend dose adjustments in pediatrics with renal impairment. Methods Initially, the PBPK model of CFT was developed in adults with normal renal function before being scaled to pediatrics, considering age-related physiological changes using GastroPlus® software. Renal impairment was modelled through optimization of tubular secretion and glomerular filtration parameters based on observed data for both adults and pediatric populations. Results The model reasonably reproduced the observed pharmacokinetic profiles and showed acceptable agreement with the data (fold error ranges 0.84–1.37) or with renal impairment (fold error ranges 0.87–1.12). When compared to children with normal renal function, the predicted AUC0−∞ in children with renal impairment increased to 1.22- and 1.89-fold for moderate and severe renal impairment, respectively. Model-informed dose recommendations were 60% and 48% of the standard pediatric dose for moderate and severe renal impairment, respectively. Conclusion This PBPK framework supports rational, model-informed dosing of CFT in pediatric patients with varying renal impairment and supports dose recommendation development for high-risk populations.

Synergistic protection: Integrating in silico and in vivo evidence for Moringa oleifera flavonoids as potent Mitigators of Deltamethrin toxicity - Muhammad Sarfraz; Irfan Baboo; Zahid Farooq; Haseeb Khaliq; Valiollah Palangi (Research in Veterinary Science, 2026)

Influence of weather patterns on ground-level ozone pollution: a 2023 summer case study in Jilin City with health risk assessment - Anees Akhtar; Chunsheng Fang; Ju Wang; Sarfraz Ahmed; Muhammad Awais Haider; Haider Ali; Muhammad Naveed; Samama Tariq (Environmental Monitoring and Assessment, 2026)

Mesenchymal stem cell-based therapeutic strategies for female infertility: current evidence and emerging targeting approaches - Muhammad Sajid; Faiz-ul Hassan; Atique Ahmed Behan; Fethi Ahmet Ozdemir; Faisal Siddique; Sarfraz Ali Fazlani; Muhammad Asif Arain; Muhammad Saif-ur Rehman (Biotechnology Letters, 2026)

Application of MnS nanoparticles in field conditions elevates morpho-physio-biochemical characteristics and oil content in Eruca sativa L. (Arugula) - Jehangir Khan; Mah Rukh; Nizakat Bibi; Joham Sarfraz Ali; Muhammad Zia (Vegetos, 2026)

Development of cytarabine-loaded pH-responsive polymeric hydrogel: an in vitro and in vivo evaluation - Shaheer Khalid; Sharjeel Adnan; Asif Mahmood; Rai Muhammad Sarfraz; Hira Ijaz; Muhammad Farooq; Bilal Haroon (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Retraction Note: Energizing sustainable development: renewable energy’s impact on South Asian environmental quality - Tamoor Azam; Isbat Alam; Muddassar Sarfraz; Muhammad Mohsin (Environmental Science and Pollution Research, 2026)

Carboxylated Graphene Oxide (CGO) Adsorbent as an Effective and Green Approach for Targeting As (III) with Improved Adsorption Characteristics - Khizar Hussain Shah; Gul Afshan Khan; Zaher Hashisho; Sadaf Sarfraz; Muhammad Fahad; Muhammad Kazim (Water, Air, & Soil Pollution, 2026)

Efficacy of Foliar-applied Chitosan Nanoparticles in Enhancing Drought Tolerance of Maize (Zea Mays L.) Through Morpho-Physiological and Biochemical Modulation - Ayesha Rukhsar; Rana Muhammad Waqas; Sarfraz Ahmed; Nian Lili; Momal Munir; Abdul Razzaq; Muhammad Arslan Asghar; Muhammad Iqbal (Journal of Soil Science and Plant Nutrition, 2026)

Modeling the interplay of cultivars, irrigation regimes, and planting dates for optimizing cotton productivity in core and non-core cotton areas of Pakistan - Raheel Osman; Muhammad Shahid Iqbal; Zareen Sarfraz; Abid Mahmood; Muhammad Rafiq Shahid; Til Feike; Lin Wang; Shenglei Fu; Syed Tahir Ata-Ul-Karim (Computers and Electronics in Agriculture, 2026)

Selection of the predator green lacewing Chrysoperla carnea for resistance to chlorfenapyr: stability, cross resistance, and fitness cost - Muhammad Abubakar; Sarfraz Ali Shad (Crop Protection, 2026)

Potential of mycorrhizal fungi in soil C sequestration under climate change scenario: current research and prospects - Muhammad Israr Khan; Moaiz Ur Rehman; Rubab Sarfraz; Ali Fakhar; Gil Won Kim (Mitigation and Adaptation Strategies for Global Change, 2026)

Rational design of facilitated-transport membranes and modules for carbon capture - Muneerah Alomar; Sidra Nawaz; Afraa Alotaibi; Muhammad Sarfraz (Chemical Engineering Journal, 2025)

Green approaches for modifying lignocellulosic features: Recent advances in reducing recalcitrance for sustainable bioethanol production - Muhammad Adnan; Adeel Ahmed; Muhammad Rafiq; Nasim Ullah; Ali Ahmad; Muhammad Sarfraz; Raza Ullah; Muzamil Ahmad; Bing Yu; Hailin Cong (Biomass and Bioenergy, 2025)

Computational identification of membrane proteins for vaccine design against drug-resistant Moraxella catarrhalis - Fizza Arshad; Rania Pervaiz; Asifa Sarfraz; Hasan Ejaz; Amal Alotaibi; Riaz Ullah; Umar Nishan; Abid Ali; Muhammad Umer Khan; Mohibullah Shah (Molecular Genetics and Genomics, 2025)

Sofosbuvir containing ph-responsive hydrogel microparticulate system: design, characterization, and biocompatibility assessment - Muhammad Aun; Muhammad Umar Ashraf; Salim Albukhaty; Umaira Rehman; Asif Mahmood; Asma Razzaq; Hira Ijaz; Rai Muhammad Sarfraz; Mohamed M. Salem; Areej Alsubaie; Mounir M. Bekhit (Journal of Pharmaceutical Innovation, 2025)

Monitoring and optimization of heavy metal phytoextraction in constructed wetlands amended with organic chelators - Mujahid Farid; Ambreen Mussarat; Muhammad Zubair; Zaki ul Zaman Asam; Ayesha Siddiqua; Wajiha Sarfraz; Roha Murtaza; Suliman Mohammed Suliman Alghanem; Haifa Abdul Aziz Sakit Alhaithloul (Environmental Monitoring and Assessment, 2025)

Investigating the toxicity risk of fourteen insecticides to a biocontrol agent Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae) compared to its prey Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) - Shoaib Hassan; Muhammad Kamran; Sarfraz Ali Shad; Safdar Khalil (Crop Protection, 2025)

Photo-activated proton-incorporation into Nd-aluminum for superionic conductors - Atif Nazar; Bushra Bibi; Sajid Rauf; Rizwan Raza; Muhammad Farrukh Sarfraz; Muhammad Khalid; Muhammad Faisal Anwar; Muhammad Ahsan Masood; Kashif Nazar; Syed Asad Abbas Bukhari; Khuloud A. Alibrahim; Bin Zhu; et al. (Chemical Engineering Journal, 2025)

Projecting future climate extremes in the glacier-fed upper indus basin using machine learning based downscaling of CMIP6 GCMs - Muhammad Amjad Saleem; Muhammad Shoaib; Sarfraz Hashim; Muhammad Shoaib; Hafiz Umar Farid; Muhammad Ismail; Mubashir Ali Ghaffar; Ahmad Mujtaba; Jinwook Lee; Muhammad Azhar Inam; Arshad Ameen (Theoretical and Applied Climatology, 2025)

Machine learning-based streamflow projections in the upper indus basin under CMIP6 climate scenarios - Muhammad Amjad Saleem; Muhammad Shoaib; Sarfraz Hashim; Muhammad Shoaib; Hafiz Umar Farid; Mubashir Ali Ghaffar; Muhammad Ismail; Arshad Ameen; Jinwook Lee; Muhammad Azhar Inam; Changhyun Jun (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Biochar and GO doped biochar powder for photocatalysis, adsorption, and latent fingermark detection - Abaid Ullah; Aliya Zahid; Shaista Ali; Aniza Latif; Muhammad Shahid; Atia Sarfraz; Muhammad Akhyar Farrukh (Journal of Water Process Engineering, 2025)

Isolation, Identification, biochemical and molecular characterization of potential source of enterotoxigenic strains of Staphylococcus aureus from the bovine raw and mastitis milk - Sikander Ali; Farzana Nazir; Muhammad Usman Ahmad; Hira Sarfraz; Abid Sarwar; Tariq Aziz; Ashwag Shami; Fahad Al-Asmari; Areej A. Alhhazmi; Abeer M. Alghamdi; Fakhria A. Al-Joufi (International Dairy Journal, 2025)

Transboundary river water quality assessment: a case study of Kabul River Basin, Pakistan - Kashif Hussain; Muhammad Shahid Iqbal; Sarfraz Munir; Hazrat Bilal (Environmental Science and Pollution Research, 2025)

Development and in vitro tuning of empagliflozin-containing dissolvable microneedle patch for enhanced transdermal delivery - Aqib Javed; Rai Muhammad Sarfraz; Asif Mahmood; Zulcaif Ahmad; Muhammad Rouf Akram; Hira Ijaz; Shammas Ali; Anam Shahzadi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Development and Optimization of Stimuli-Responsive Fenugreek/Carrageenan-Co-poly (Methacrylate) Hydrogel Matrices for Controlled Delivery of 5-Fluorouracil - Muhammad Arslan; Muhammad Umer Ashraf; Ayman M. Al-Qaaneh; Aysha Aslam; Asif Mahmood; Hira Ijaz; Rai Muhammad Sarfraz; Mohamed M. Salem; Milad A. Mezher; Mounir M. Bekhit (AAPS PharmSciTech, 2025)

Conserving the genetic resources of Rita rita: A GIS-mapping based approach - Muhammad Waseem; Khalid Abbas; Taqwa Safdar; Muhammad Sarfraz Ahmed; Noreen Asghar; Zahida Rasheed; Sumra Naz (Fisheries Research, 2025)

Polycyclic aromatic hydrocarbons (PAHs) occurrences in water bodies, extraction techniques, detection methods, and standardized guidelines for PAHs in aqueous solutions - Rana Muhammad Mubeen Muhsin; Teh Sabariah Binti Abd Manan; Joseph Bidai; Muhammad Sarfraz Ahmad Mangat; Zarimah Mohd Hanafiah; Adel Gohari; Naveed Ahmad; Farooq Ahmad; Salmia Beddu; Nur Liyana Mohd Kamal; Daud Mohamad; Shatha Aser Hamad Aldala'in; et al. (Science of The Total Environment, 2025)

Comparative biology of chlorantraniliprole selected and unselected Chrysoperla carnea (Stephens) populations: Stability of resistance, inheritance mode, and realized heritability - Muhammad Abubakar; Sarfraz Ali Shad (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Expression and characterization of the immunogenicity of rec-gp45 of Babesia bigemina using cattle - Zia-Ul-Rehman; Sarfraz-ur-Rahman; Kamran Ashraf; Muhammad Suleman; Sikandar Ali; Muhammad Imran Rashid (Tropical Animal Health and Production, 2025)

Organic Amendments Enhanced Phytoremediation, Physio-Chemical Functions, Growth and Productivity of Zea mays L. in Diesel-Contaminated Soil - Muhammad Sarfraz Ahmad; Ghazala; Fahd Rasul; Muhammad Ibrahim; Abid Mahmood (Journal of Soil Science and Plant Nutrition, 2025)

Genetic analysis of chlorantraniliprole resistance in the non-target bio-control agent Trichogramma chilonis - Muhammad Kamran; Muhammad Ahmad; Sarfraz Ali Shad (Chemosphere, 2025)

Peptide-based vaccine design against Hendra virus through immunoinformatics approach - Asifa Sarfraz; Irfa Chaudhary; Fizza Arshad; Muhammad Shehroz; Asia Perveen; Umar Nishan; Abid Ali; Riaz Ullah; Abdelaaty A. Shahat; Aqal Zaman; Mohibullah Shah (Veterinary Immunology and Immunopathology, 2025)

Enhancing phytoremediation in chamomile (Matricaria chamomilla L.) using moringa extract and zero-valent iron nanoparticles - Urooj Ansar Mughal; Mujahid Farid; Wajiha Sarfraz; Mostafa A. Abdel-Maksoud; Abdul Malik; Zaki ul Zaman Asam; Mohsin Abbas; Muhammad Zubair; Sabiha Fatima; Noreen Khalid (South African Journal of Botany, 2025)

Computer-aided rational design of a mRNA vaccine against Guanarito mammarenavirus - Mohibullah Shah; Asifa Sarfraz; Muhammad Shehroz; Asia Perveen; Samavia Jaan; Aqal Zaman; Umar Nishan; Arlindo A. Moura; Riaz Ullah; Zafar Iqbal; Mohamed A. Ibrahim (Biotechnology Letters, 2025)

Development and In-Vitro Tuning of Piperine Containing Solid Lipid Microparticles for the Treatment of Rheumatoid Arthritis - Muneeba Aziz; Sajid Bashir; Rai Muhammad Sarfraz; Hira Ijaz; Asif Mahmood; Zulcaif; Bilal Haroon; Milad A. Mezher; Mohamed M. Salem; Sami Al Zahrani; Mounir M. Bekhit (AAPS PharmSciTech, 2025)

Human Plasma-Derived Exosomes: A Promising Carrier System for the Delivery of Hydroxyurea to Combat Breast Cancer - Wajeeha Khalid; Afeefa Aslam; Nadeem Ahmed; Muhammad Sarfraz; Jawad Akbar Khan; Sabeeh Mohsin; Muhammad Shahid Riaz Rajoka; Imran Nazir; Muhammad Imran Amirzada (AAPS PharmSciTech, 2025)

Dosage Optimization Using Physiologically Based Pharmacokinetic Modeling for Pediatric Patients with Renal Impairment: A Case Study of Meropenem - Najia Rahim; Muhammad Sarfraz; Abubakar Bello; Syed Baqir Shyum Naqvi (AAPS PharmSciTech, 2025)

Anthranilic diamide compatibility with the parasitoid Trichogramma chilonis Ishii (Hymenoptera: Trichogrammatidae): Based on Toxicity, Two-sex life table and ecological parameters - Muhammad Kamran; Muhammad Ahmad; Sarfraz Ali Shad (Crop Protection, 2025)

Toxicity and fitness evaluation of Chrysoperla carnea resistant strains on cotton mealy bug Phenacoccus solenopsis Tinsely - Mashahood Ali Khan; Sarfraz Ali Shad; Fehmina Atta; Muhammad Gul Zaman; Muhammad Abubakar (Crop Protection, 2025)

Biochemical mechanism of emamectin benzoate resistance in citrus mealybug, Planococcus citri (Hemiptera: Pseudococcidae); cross-resistance and realized heritability - Muhammad Mudassir Mansoor; Sarfraz Ali Shad; Abu Bakar Muhammad Raza (International Journal of Tropical Insect Science, 2024)

Field validation of NDVI to identify crop phenological signatures - Muhammad Tousif Bhatti; Hammad Gilani; Muhammad Ashraf; Muhammad Shahid Iqbal; Sarfraz Munir (Precision Agriculture, 2024)
Purpose and Methods Crop identification using remotely sensed imagery provides useful information to make management decisions about land use and crop health. This research used phonecams to acquire the Normalized Difference Vegetation Index (NDVI) of various crops for three crop seasons. NDVI time series from Sentinel (L121-L192) images was also acquired using Google Earth Engine (GEE) for the same period. The resolution of satellite data is low therefore gap filling and smoothening filters were applied to the time series data. The comparison of data from satellite images and phenocam provides useful insight into crop phenology. The results show that NDVI is generally underestimated when compared to phenocam data. The Savitzky-Golay (SG) and some other gap filling and smoothening methods are applied to NDVI time series based on satellite images. The smoothened NDVI curves are statistically compared with daily NDVI series based on phenocam images as a reference. Results The SG method has performed better than other methods like moving average. Furthermore, polynomial order has been found to be the most sensitive parameter in applying SG filter in GEE. Sentinel (L121-L192) image was used to identify wheat during the year 2022–2023 in Sargodha district where experimental fields were located. The Random Forest Machine Leaning algorithm was used in GEE as a classifier. Conclusion The classification accuracy has been found 97% using this algorithm which suggests its usefulness in applying to other areas with similar agro-climatic characteristics.

Correction: Seed Priming with Iron Oxide Nanoparticles Ameliorates As Toxicity by Decreasing Organic Acid Exudation Pattern and Modulating Specific Gene Expression in Rapeseed (Brassica napus L.) - Rana M. Alshegaihi; Manar Fawzi Bani Mfarrej; Aishah Alatawi; Khairiah Mubarak Alwutayd; Salem Albalawi; Saba Saleem; Muhammad Hamzah Saleem; Wajiha Sarfraz; Shafaqat Ali; Amany H. A. Abeed (Journal of Plant Growth Regulation, 2024)

Seed Priming with Iron Oxide Nanoparticles Ameliorates As Toxicity by Decreasing Organic Acid Exudation Pattern and Modulating Specific Gene Expression in Rapeseed (Brassica napus L.) - Rana M. Alshegaihi; Manar Fawzi Bani Mfarrej; Aishah Alatawi; Khairiah Mubarak Alwutayd; Salem Albalawi; Saba Saleem; Muhammad Hamzah Saleem; Wajiha Sarfraz; Shafaqat Ali; Amany H. A. Abeed (Journal of Plant Growth Regulation, 2024)

Design and Evaluation of Inorganic/Organic Hybrid Bio-composite for Site-Specific Oral Delivery of Darifenacin - Wafa Ishaq; Attia Afzal; Muhammad Farooq; Muhammad Sarfraz; Sherjeel Adnan; Hammad Ahmed; Muhammad Waqas; Zainab Safdar (AAPS PharmSciTech, 2024)
Benign hyperplasia (BHP) is a common disorder that affects men over the age of 60 years. Transurethral resection of the prostate (TURP) is the gold standard for operative treatment, but a range of drugs are also available to improve quality of life and to reduce BHP-associated urinary tract infections and complications. Darifenacin, an anti-muscarinic agent, has been found effective for relieving symptoms of overactive bladder associated with BHP, but the drug has poor solubility and bioavailability, which are major challenges in product development. An inorganic/organic bio-composite with gastric pH-resistant property was synthesized for the targeted oral delivery of Darifenacin to the lower gastrointestinal tract (GIT). This development was accomplished through co-precipitation of calcium carbonate in quince seed-based mucilage. The FTIR, XRD, DSC, and TGA results showed good drug-polymer compatibility, and the SEM images showed calcite formation in the quince hydrogel system. After 72 h, the drug release of 34% and 75% were observed in acidic (0.1N HCl) and 6.8 pH phosphate buffer, respectively. A restricted/less drug was permeated through gastric membrane (21.8%) as compared to permeation through intestinal membrane (65%.) The developed composite showed significant reduction in testosterone-induced prostatic hyperplasia (2.39 ± 0.12***) as compared to untreated diseased animal group. No sign of organ toxicity was observed against all the developed composites. In this study, we developed an inorganic–organic composite system that is highly biocompatible and effective for targeting the lower GIT, thereby avoiding the first-pass metabolism of darifenacin. Graphical Abstract

Realized heritability, inheritance, and mechanism of chlorfenapyr resistance in biocontrol agent, Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae): A step towards sustainable pest management - Muhammad Abubakar; Sarfraz Ali Shad (Chemosphere, 2024)

Cenchrus ciliaris L. ameliorates cigarette-smoke induced acute lung injury by reducing inflammation and oxidative stress - Muhammad Irfan Aslam; Saad Touqeer; QurratUlAin Jamil; Muhammad Irfan Masood; Adeel Sarfraz; Shafaat Yar Khan; Muhammad Saeed Jan; Sulaiman Mohammed Abdullah Alnasser; Ashfaq Ahmad; Fatima Aslam; Shahid Muhammad Iqbal (South African Journal of Botany, 2024)

Multiomics analysis reveals a substantial decrease in nanoplastics uptake and associated impacts by nano zinc oxide in fragrant rice (Oryza sativa L.) - Muhammad Imran; Muhammad Junaid; Sarfraz Shafiq; Shulin Liu; Xiaoyuan Chen; Jun Wang; Xiangru Tang (Journal of Hazardous Materials, 2024)

Treatment of marble industry wastewater by Brassica napus (L.) under oxalic acid amendment: efficacy as fodder and carcinogenic risk assessment - Arwa Abdulkreem AL-Huqail; Ibtisam Mohammed Alsudays; Suliman Mohammed Suliman Alghanem; Ramzan Anwar; Mujahid Farid; Wajiha Sarfraz; Muhammad Zubair; Zaki Ul Zaman Asam; Mohsin Abbas; Muhammad Rizwan (Environmental Science and Pollution Research, 2024)

Correction to: Fitness cost, cross-resistance, instability and realized heritability of deltamethrin resistance in Tribolium castaneum (Coleoptera: Tenebrionidae) - Iqra Khalid; Muhammad Kamran; Sarfraz Ali Shad; Mishal Khizar (International Journal of Tropical Insect Science, 2024)

Eocene nannofossils and paleoenvironmental reconstruction of the Kuldana Formation in Yadgar area, Muzaffarabad, northern Pakistan - Amir Shahzad; Jahanzeb Khan; Muhammad Hanif; Claudia Baumgartner-Mora; Yasir Sarfraz; Khawaja Shoaib Ahmed; Muhammad Tayyib Riaz; Peter O. Baumgartner; Munir ul Hassan Munir; Adnan Wazir (Palaeoworld, 2024)

SPOTLIGHT: NAC transcription factor elevates iron content in maize: A promising solution to combat iron deficiency - Muhammad Imran; Sarfraz Shafiq; Emilie Widemann (Journal of Plant Physiology, 2024)

Ecotoxicological risk assessment of combined insecticidal and thermal stresses on Trichogramma chilonis - Muhammad Ahmad; Muhammad Kamran; Muhammad Nabeel Abbas; Sarfraz Ali Shad (Journal of Pest Science, 2024)

Partitioning carbon dioxide emissions from soil organic matter and urea in warm and cold cropping seasons - Muhammad Israr Khan; Rubab Sarfraz; Taeyoung Kim; Hye-Jin Park; Pil Joo Kim; Gil Won Kim (Atmospheric Pollution Research, 2024)

Genome-wide association study reveals novel genes on different chromosomal positions regulating boll weight in upland cotton (Gossypium hirsutum L.) - Zubair Iqbal; Muhammad Shahid Iqbal; Salman Alamery; Khurram Shehzad; Qamar U. Zaman; Safira Attacha; Zareen Sarfraz; Mian Faisal Nazir; Daowu Hu; Muhammad Mubashar Zafar; Aqib Zeb; Shoupuhe; et al. (Genetic Resources and Crop Evolution, 2024)

Mitigating chromium toxicity in rice (Oryza sativa L.) via ABA and 6-BAP: Unveiling synergistic benefits on morphophysiological traits and ASA-GSH cycle - Khairiah Mubarak Alwutayd; Suliman Mohammed Suliman Alghanem; Rahaf Alwutayd; Sameera A. Alghamdi; Nadiyah M. Alabdallah; Rahmah N. Al-Qthanin; Wajiha Sarfraz; Noreen Khalid; Nayab Naeem; Baber Ali; Muhammad Hamzah Saleem; Sadia Javed; et al. (Science of The Total Environment, 2024)

CRISPR/Cas9-based genome editing: A revolutionary approach for crop improvement and global food security - Ghulam Muha-Ud-Din; Faizan Ali; Akhtar Hameed; Syed Atif Hasan Naqvi; Mir Muhammad Nizamani; Muhammad Jabran; Sohaib Sarfraz; Wang Yong (Physiological and Molecular Plant Pathology, 2024)

Minimizing the total petroleum hydrocarbon contaminants in biochar derived from agricultural byproducts - Muhammad Israr Khan; Rubab Sarfraz; Pil Joo Kim; Gil Won Kim (Journal of Cleaner Production, 2024)

Fitness cost, cross-resistance, instability and realized heritability of deltamethrin resistance in Tribolium castaneum (Coleoptera: Tenebrionidae) - Iqra Khalid; Muhammad Kamran; Sarfraz Ali Shad; Mishal Khizar (International Journal of Tropical Insect Science, 2023)

Fabrication and Evaluation of Differential Release Bilayer Tablets of Clarithromycin and Levofloxacin by 3D Printing - Qazi Amir Ijaz; Sumera Latif; Sumaira Irum Khan; Memoona Rashid; Hafsa Afzal; Nasrullah Jan; Zeeshan Javaid; Muhammad Sarfraz; Amjad Hussain; Muhammad Sohail Arshad; Nadeem Irfan Bukhari; Nasir Abbas (Journal of Pharmaceutical Innovation, 2023)

Heavy metals contamination in vegetables irrigated with wastewater: a case study of underdeveloping regions of Pakistan - Ana Aslam; Asifa Naz; Syed Shahid Hussain Shah; Farah Rasheed; Raheela Naz; Amina Kalsom; Nisa Mukhtar; Abid Niaz; Muhammad Aftab; Irfan Rasheed; Muhammad Arfan Ul Haq; Muhammad Arif; et al. (Environmental Geochemistry and Health, 2023)

Inheritance of esterases based spiromesifen resistance in Musca domestica Linnaeus (Diptera: Muscidae) - Hafiz Muhammad Usama Khan; Rizwan Mustafa Shah; Sarfraz Ali Shad (International Journal of Tropical Insect Science, 2023)

Impact and mitigation of lead, cadmium and micro/nano plastics in fragrant rice - Muhammad Imran; Muhammad Ansar Farooq; Ayesha Batool; Sarfraz Shafiq; Muhammad Junaid; Jun Wang; Xiangru Tang (Environmental Pollution, 2023)

RETRACTED ARTICLE: Energizing sustainable development: renewable energy’s impact on South Asian environmental quality - Tamoor Azam; Isbat Alam; Muddassar Sarfraz; Muhammad Mohsin (Environmental Science and Pollution Research, 2023)

Forecasting potential risk for development of spiromesifen resistance in Tetranychus urticae (Koch): its genetics and cross-resistance - Muhammad Kamran; Zahid Mehmood Sarwar; Ayyan Umer; Sarfraz Ali Shad; Muhammad Abubakar (International Journal of Tropical Insect Science, 2023)

Identification, characterization and expression profiling of salt-stress responsive proteinase inhibitor in Gossypium arboreum L. - Muhammad Naveed Shahid; Sarfraz Kiani; Bushra Rashid; Tayyab Husnain (South African Journal of Botany, 2023)

Fabrication and Evaluation of Anticancer Potential of Eugenol Incorporated Chitosan-Silver Nanocomposites: In Vitro, In Vivo, and In Silico Studies - Hamid Saeed Shah; Sumera Zaib; Muhammad Sarfraz; A. Alhadhrami; Mohamed M. Ibrahim; Aamir Mushtaq; Faisal Usman; Memoona Ishtiaq; Muhammad Sajjad; Hafiz Muhammad Mazhar Asjad; Umar Farooq Gohar (AAPS PharmSciTech, 2023)

Lupeol, a plant triterpenoid mitigates salt induced stress: growth and antioxidative response of Brassica nigra under in vitro condition - Muhammad Zia; Joham Sarfraz Ali; Saad Hanif; Anila Sajjad; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Phytochemical, biological, and in-silico analysis of Colutea armata Hemsl. & Lace: A possible source of bioactive natural compounds - Ayisha Khalid; Samina Afzal; Farhan Abbas; Iftikhar Afzal; Muhammad Iqbal; Sarfraz Ahmad; Siddique Akber Ansari; Hamad M. Alkahtani; Tahir Ali Chohan; Umair Khurshid; Hammad Saleem; Carlos Leonardo Cespedes-Acuna (South African Journal of Botany, 2023)

Negative Impact of Unstable Spiromesifen Resistance on Fitness of Tetranychus urticae (Acari: Tetranychidae) - Muhammad Abubakar; Ayyan Umer; Sarfraz Ali Shad; Zahid Mehmood Sarwar; Muhammad Kamran (Neotropical Entomology, 2023)

Enhancing carbon capture efficiency of zeolite-embedded polyether sulfone mixed-matrix membranes via annealing process - Aamir Sohail; Muhammad Sarfraz; Sidra Nawaz; Zaman Tahir (Journal of Cleaner Production, 2023)

Dose optimization of silicon for boosting arbuscular mycorrhizal fungi colonization and cadmium stress mitigation in maize (Zea mays L.) - Ubaid Ullah Zia; Abdul Rehman Niazi; Zahoor Ahmad; Hesham F. Alharby; Ejaz Ahmad Waraich; Asim Abbasi; Muhammad Aamir Iqbal; Sarfraz Ahmed; Shozab Hina (Environmental Science and Pollution Research, 2023)

Recent Innovations in Non-dairy Prebiotics and Probiotics: Physiological Potential, Applications, and Characterization - Fasiha Fayyaz Khan; Asma Sohail; Shakira Ghazanfar; Asif Ahmad; Aayesha Riaz; Kashif Sarfraz Abbasi; Muhammad Sohail Ibrahim; Mohammad Uzair; Muhammad Arshad (Probiotics and Antimicrobial Proteins, 2023)

Integrative Evaluation of the Ecological Hazards by Microplastics and Heavy Metals in Wetland Ecosystem - Shanza Zaka; Muhammad Aqeel; Adeel Mahmood; Ali Noman; Zarrin Fatima Rizvi; Wajiha Sarfraz; Aisha Nazir; Komal Arshad; Noreen Khalid (Bulletin of Environmental Contamination and Toxicology, 2023)

Bird community structure is driven by urbanization level, blue-green infrastructure configuration and precision farming in Taizhou, China - Yixue Chen; Muhammad Awais Rasool; Sarfraz Hussain; Shuang Meng; Yipeng Yao; Xue Wang; Yuhong Liu (Science of The Total Environment, 2023)

Prospects of antimicrobial peptides as an alternative to chemical preservatives for food safety - Iqra Kamal; Usman Ali Ashfaq; Sumreen Hayat; Bilal Aslam; Muhammad Hassan Sarfraz; Hamna Yaseen; Muhammad Shahid Riaz Rajoka; Asad Ali Shah; Mohsin Khurshid (Biotechnology Letters, 2023)

Influence of rangeland protection and seasonal grazing on aboveground vegetation, forage quality and weight gain of small ruminants — a study in Thar Desert, Pakistan - Muhammad Islam; Abdul Razzaq; Sawsan Hassan; Muhammad Zubair; Muhammad Waseem Kalroo; Attaullah Khan; Shamim Gul; Sarfraz Ahmad; Barbara Ann Rischkowsky; Mounir Louhaichi (Journal of Mountain Science, 2023)

Ecological health risk assessment of microplastics and heavy metals in sediments, water, hydrophytes (Alternanthera philoxeroides, Typha latifolia, and Ipomoea carnea), and fish (Labeo rohita) in Marala wetlands in Sialkot, Pakistan - Komal Arshad; Muhammad Aqeel; Ali Noman; Atia Nazir; Adeel Mahmood; Zarrin Fatima Rizvi; Wajiha Sarfraz; Sajjad Hyder; Shanza Zaka; Noreen Khalid (Environmental Science and Pollution Research, 2023)

Foliar application of silicon-based nanoparticles improve the adaptability of maize (Zea mays L.) in cadmium contaminated soils - Sarfraz Ahmed; Muhammad Iqbal; Zahoor Ahmad; Muhammad Aamir Iqbal; Arkadiusz Artyszak; Ayman E. L. Sabagh; Hesham F. Alharby; Akbar Hossain (Environmental Science and Pollution Research, 2023)

Polygenic and autosomally inherited dimethoate resistance in Amrasca biguttula biguttula with no cross-resistance to bifenthrin, imidacloprid, and chlorfenapyr - Iqra Khalid; Muhammad Mohsin; Muhammad Abubakar; Sarfraz Ali Shad; Muhammad Binyameen (Crop Protection, 2023)

Role of agricultural resource sector in environmental emissions and its explicit relationship with sustainable development: Evidence from agri-food system in China - Muddassar Sarfraz; Kashif Iqbal; Yichu Wang; Muhammad Shoaib Bhutta; Zain ul Abidin Jaffri (Resources Policy, 2023)

Effect of autosomally inherited, incompletely dominant, and unstable spinosad resistance on physiology of Tribolium castaneum (Coleoptera: Tenebrionidae): Realized heritability and cross-resistance - Iqra Khalid; Muhammad Kamran; Muhammad Abubakar; Mishal Khizar; Sarfraz Ali Shad (Journal of Stored Products Research, 2023)

Correction to: Monitoring and assessment of resistance to insecticides in the lacewing Chrysoperla carnea (Stephens) - Muhammad M. Mansoor; Sarfraz A. Shad (Environmental Monitoring and Assessment, 2023)

Chemical composition, antibacterial and antioxidative activities of Monotheca buxifolia (Falc.) A. DC leaves essential oil - Joham Sarfraz Ali; Muhammad Azeem; Abdul Mannan; Muhammad Zia (Natural Product Research, 2022)

Antioxidant, antimicrobial, enzyme inhibition, and cytotoxicity guided investigation of Sideroxylon mascatense (A.DC.) T.D. Penn. leaves extracts - Joham Sarfraz Ali; Naheed Riaz; Abdul Mannan; Muhammad Latif; Muhammad Zia (Natural Product Research, 2022)

Trichlorfon tolerance, risk assessment, and a cross-resistance trend to four other insecticides in Bactrocera zonata (Saunders) - Mashahood Ali Khan; Muhammad Kamran; Sarfraz Ali Shad; Muhammad Anees (Phytoparasitica, 2022)

Does energy use and economic growth allow for environmental sustainability? An empirical analysis of Pakistan - Muhammad Mohsin; Sobia Naseem; Muddassar Sarfraz; Muhammad Zia-UR-Rehman; Sajjad Ahmad Baig (Environmental Science and Pollution Research, 2022)

Electrical resistivity tomography for delineating groundwater potential zones in fractured metasedimentary rocks, Lesser Himalayas, Pakistan - Muhammad Farooq; Umair Bin Nisar; Sarfraz Khan; Tarib Jalees; Muhammad Rizwan Mughal; Liaqat Ali; Toqeer Ahmed (Journal of Earth System Science, 2022)

Status of insecticide resistance in Plutella xylostella (Linnaeus) (Lepidoptera: Plutellidae) from 1997 to 2019: cross-resistance, genetics, biological costs, underlying mechanisms, and implications for management - Ansa Banazeer; Muhammad Babar Shahzad Afzal; Shoaib Hassan; Mamuna Ijaz; Sarfraz Ali Shad; José Eduardo Serrão (Phytoparasitica, 2022)

A blessing in disguise: new insights on the effect of COVID-19 on the carbon emission, climate change, and sustainable environment - Muddassar Sarfraz; Muhammad Mohsin; Sobia Naseem (Environmental Science and Pollution Research, 2022)

Erratum to: Impact of rangeland enclosure and seasonal grazing on protected and unprotected rangelands in Chakwal region, Pakistan - Muhammad Islam; Abdul Razzaq; Muhammad Zubair; Sawsan Hassan; Sarfraz Ahmad; Shamim Gul; Barbara Rischkowsky; Mounir Louhaichi (Journal of Mountain Science, 2022)
The article “Impact of rangeland enclosure and seasonal grazing on protected and unprotected rangelands in Chakwal region, Pakistan”, written by ISLAM Muhammad, RAZZAQ Abdul, ZUBAIR Muhammad, HASSAN Sawsan, AHMAD Sarfraz, GUL Shamim, RISCHKOWSKY Barbara and LOUHAICHI Mounir, was originally published electronically on the publisher’s internet portal (currently SpringerLink) on 27 December 2021 without open access. With the author’s decision to opt for open choice the copyright of the article changed in 02/2022 to © The Author(s) 2022. This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons license, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons license and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/ . The original article has been corrected.

Biochemical resistance characterization to chlorpyrifos, acetamiprid, spinosad, and emamectin benzoate in Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) from Pakistan - Bushra Saddiq; Muhammad Babar Shahzad Afzal; Ashfaq Ahmad Sial; Naeem Abbas; Sarfraz Ali Shad; Asif Sajjad; Sajjad Ali (Phytoparasitica, 2022)

Effects of interspecific competition between Aedes aegypti and Culex quinquefasciatus on their life history traits - Daniyal Ahmad; Muhammad Waqas Sumra; Rizwan Mustafa Shah; Mehboob Alam; Sarfraz Ali Shad; Unsar Naeem-Ullah; Muhammad Binyameen (International Journal of Tropical Insect Science, 2022)

The influence of energy consumption and economic growth on environmental degradation in BRICS countries: an application of the ARDL model and decoupling index - Sobia Naseem; Muhammad Mohsin; Muhammad Zia-UR-Rehman; Sajjad Ahmad Baig; Muddassar Sarfraz (Environmental Science and Pollution Research, 2022)

Risk assessment of cyromazine and methoxyfenozide resistance suggests higher additive genetic but lower environmental variation supporting quick resistance development in non-target Chrysoperla carnea (Stephens) - Muhammad Mudassir Mansoor; Sarfraz Ali Shad (Environmental Monitoring and Assessment, 2022)

Impact of rangeland enclosure and seasonal grazing on protected and unprotected rangelands in Chakwal region, Pakistan - Muhammad Islam; Abdul Razzaq; Muhammad Zubair; Sawsan Hassan; Sarfraz Ahmad; Shamim Gul; Barbara Rischkowsky; Mounir Louhaichi (Journal of Mountain Science, 2022)
Scrub rangelands support livestock grazing and provide ecosystem services to their inhabitants. The present study was conducted in Chakwal, an important tract of the Pothwar Plateau, which sustains herds of small domestic and nomadic ruminants. Urbanization and uncontrolled grazing practices have reduced rangeland productivity and increased soil erosion and resulted in poor land conditions. This study assessed the influence of two years of rangeland protection on aboveground vegetation biomass and the chemical composition of plants and aimed to determine the influence of seasonal grazing on the live-weight gain of small ewes. Using the line intercept method, vegetation data from protected and unprotected plots in 2015 and 2016 were collected at two sites, Dhulli and Begal. Vegetation cover was assessed from images using VegMeasure. Results showed that protected study sites displayed higher vegetation biomass (834 and 690 kg ha -1 ) compared to the unprotected study site (477 and 326 kg ha -1 ) during April and August of both years. In the seasonal grazing trial, the experimental ewes that grazed on protected rangelands showed higher live-weight gain (33–63 g day -1 ) compared to live weight of ewes (17–21 g day -1 ) that grazed on unprotected rangelands during the experimental period of 127 days at both sites. The results suggest that the Chakwal rangeland has tremendous potential to improve vegetation productivity but modern livestock management and seasonal grazing practices are needed to improve carrying capacity and livestock productivity.

Modeling the relationship between carbon emissions and environmental sustainability during COVID-19: a new evidence from asymmetric ARDL cointegration approach - Muddassar Sarfraz; Muhammad Mohsin; Sobia Naseem; Amit Kumar (Environment, Development and Sustainability, 2021)

Trichlorfon resistance: its stability and impacts on biological parameters of Bactrocera zonata (Diptera: Tephritidae) - Muhammad Abubakar; Haider Ali; Sarfraz Ali Shad; Muhammad Anees; Muhammad Binyameen (Applied Entomology and Zoology, 2021)

Sulfate-Based Fertilizers Regulate Nutrient Uptake, Photosynthetic Gas Exchange, and Enzymatic Antioxidants to Increase Sunflower Growth and Yield Under Drought Stress - Bilal Ahamid Shafiq; Fahim Nawaz; Sadia Majeed; Muhammad Aurangzaib; Abdullah Al Mamun; Muhammad Ahsan; Khawaja Shafique Ahmad; Muhammad Asif Shehzad; Muqarrab Ali; Sarfraz Hashim; Tanveer ul Haq (Journal of Soil Science and Plant Nutrition, 2021)
The challenging impact of drought to agricultural productivity requires the adoption of mitigation strategies with a better understanding of underlying mechanisms responsible for drought tolerance. The present study aimed at investigating the effects of sulfur-based fertilizers on mitigation of drought stress in sunflower. Sulfate-containing fertilizers, viz., ammonium sulfate, zinc sulfate, magnesium sulfate, potassium sulfate, and gypsum, were initially evaluated at two different rates (10 and 20 mg kg −1 soil equivalent to 20 and 40 kg ha −1 , respectively) for nutrient uptake and growth-promoting traits in sunflower seedlings (cv. Hysun-33). The best performing fertilizer (gypsum) was then selected to evaluate the response of sunflower under drought stress imposed at flowering stage for three weeks (25–30% water holding capacity). Results indicated significant amelioration of drought stress with higher activity of photosynthetic apparatus, upregulation of antioxidative enzymes, and increased achene yield by gypsum application. In comparison to control, gypsum-treated plants (20 mg kg −1 soil) exhibited higher water status (32%), leaf photosynthetic rate (29%), transpiration rate (67%), and stomatal conductance (118%) under drought stress. The antioxidant enzyme activities of catalase, guaiacol peroxidase, and superoxide dismutase were also increased by 67%, 62%, and 126%, respectively, resulting in higher achene yield (19%) under water-deficit conditions. This study indicates that the application of sulfur-based fertilizers (gypsum) can be used to induce drought tolerance and obtain high sunflower yields under drought stress, and furthermore, it is a cost-effective strategy resulting in high benefit–cost ratio with respect to no gypsum application.

Geotechnical investigation and landslide susceptibility assessment along the Neelum road: a case study from Lesser Himalayas, Pakistan - Khawaja Shoaib Ahmed; Muhammad Basharat; Muhammad Tayyib Riaz; Yasir Sarfraz; Amir Shahzad (Arabian Journal of Geosciences, 2021)

Monitoring and assessment of resistance to insecticides in the lacewing Chrysoperla carnea (Stephens) - Muhammad M. Mansoor; Sarfraz A. Shad (Environmental Monitoring and Assessment, 2021)

Shadow detection of the satellite images of earth using ratio image pixels - Suhaib Musleh; Muhammad Sarfraz; Hazem Raafat (Earth Science Informatics, 2021)

Correction to: Site response studies in Peshawar using the Nakamura technique of HVSR - Sarfraz Khan; Muhammad Waseem; Shoaib Jan (Arabian Journal of Geosciences, 2021)

Role of fruit volatiles of different guava varieties in attraction and oviposition behaviors of peach fruit fly, Bactrocera zonata Saunders - Muhammad Binyameen; Abdul Hamid; Imran Afzal; Muhammad Sajjad; Muhammad Azeem; Syed Muhammad Zaka; Zahid Mehmood Sarwar; Sarfraz Ali Shad; Thomas C. Baker; Fredrik Schlyter (Arthropod-Plant Interactions, 2021)

Site response studies in Peshawar using the Nakamura technique of HVSR - Sarfraz Khan; Muhammad Waseem; Shoaib Jan (Arabian Journal of Geosciences, 2021)

Landslides assessment using geophysical and passive radon exhalation detection techniques in Murree Hills, northern Pakistan: Implication for environmental hazard assessment - Khawar Ashfaq Ahmed; Sarfraz Khan; Mahmood Sultan; Umair Bin Nisar; Muhammad Rizwan Mughal; Shahid Nadeem Qureshi (Journal of Earth System Science, 2020)

Characterization of dimethoate resistance in Oxycarenus hyalinipennis (Costa): resistance selection, cross-resistance to three insecticides and mode of inheritance - Ansa Banazeer; Muhammad Babar Shahzad Afzal; Sarfraz Ali Shad (Phytoparasitica, 2020)

First report of Curvularia verruculosa causing leaf spot disease of grape (Vitis vinifera) in Afghanistan - Nasir Ahmed Rajput; Hussainullah; Chao Huo; JiFen Cao; Muhammad Atiq; Rana Muhammad Atif; Abdul Mubeen Lodhi; Rehana Naz Syed; Sohaib Sarfraz; Akhtar Hameed; Zhijian Zhao (Journal of Plant Pathology, 2020)

Integrated Application of Organic Amendments with Alcaligenes sp. AZ9 Improves Nutrient Uptake and Yield of Maize (Zea mays) - Azhar Hussain; Maqshoof Ahmad; Muhammad Zahid Mumtaz; Sajjad Ali; Rubab Sarfraz; Muhammad Naveed; Moazzam Jamil; Christos A. Damalas (Journal of Plant Growth Regulation, 2020)

Probabilistic Seismic Hazard Assessment of Pakistan Territory Using an Areal Source Model - Muhammad Waseem; Sarfraz Khan; M. Asif Khan (Pure and Applied Geophysics, 2020)

Signifying the imperative nexus between climate change and information and communication technology development: a case from Pakistan - Khurram Shehzad; Liu Xiaoxing; Muddassar Sarfraz; Muhammad Zulfiqar (Environmental Science and Pollution Research, 2020)

Climate change–induced human conflicts and economic costs in Pakistani Punjab - Khuda Bakhsh; Karim Abbas; Sarfraz Hassan; Muhammad Asim Yasin; Rafaqet Ali; Najid Ahmad; Muhammad Waqas Alam Chattha (Environmental Science and Pollution Research, 2020)

Linking environment, malaria, and agricultural returns: a labor time use analysis at different stages of production using 3SLS - Sobia Rose; Muhammad Faisal Ali; Khuda Bakhsh; Muhammad Ashfaq; Sarfraz Hassan (Environmental Science and Pollution Research, 2020)

Litter decay in rangeland sites with varying history of human disturbance: a study with Hazargangi Chiltan mountain - Imran Khan; Shamim Gul; Sarfraz Ahmad; Gul Bano Rehman; Agha Waqar Yunus; Iram Gul; Imran Ali; Ali Akbar; Muhammad Islam (Journal of Mountain Science, 2020)

Temperature trends and elevation dependent warming during 1965–2014 in headwaters of Yangtze River, Qinghai Tibetan Plateau - Naveed Ahmed; Gen-xu Wang; Adeyeri Oluwafemi; Sarfraz Munir; Zhao-yong Hu; Aamir Shakoor; Muhammad Ali Imran (Journal of Mountain Science, 2020)

Antimicrobial, cytotoxic, phytochemical and biological properties of crude extract and solid phase fractions of Monotheca buxifolia - Joham Sarfraz Ali; Ihsan Khan; Muhammad Zia (Advances in Traditional Medicine, 2020)

Microzonation map of the Abbottabad basin and immediate surroundings - Sarfraz Khan; Muhammad Waseem; Muhammad Asif Khan; Zahid Hussain; Waqas Ahmed; Ahmad Hamad Khaliq; Nisar Bin Umair; Mian Luqman Hussain (Journal of Seismology, 2020)

Seismic sources for southern Pakistan and seismic hazard assessment of Karachi - Muhammad Waseem; Muhammad Asif Khan; Sarfraz Khan (Natural Hazards, 2019)

Spinosad resistance selected in the laboratory strain of Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae): studies on risk assessment and cross-resistance patterns - Ansa Banazeer; Muhammad Babar Shahzad Afzal; Mamuna Ijaz; Sarfraz Ali Shad (Phytoparasitica, 2019)

First report of Geotrichum candidum causing postharvest sour rot of carrot in Punjab, Pakistan - Akhtar Hameed; Muhammad Waqar Alam; Abdul Rehman; Khalid Naveed; Muhammad Atiq; Nasir Ahmed Rajput; Sohaib Sarfraz; Nadia Liaqat; Faizan Ahmad Tahir (Journal of Plant Pathology, 2019)

Seismic hazard assessment of Afghanistan - Muhammad Waseem; Abdul Lateef; Irshad Ahmad; Sarfraz Khan; Waqas Ahmed (Journal of Seismology, 2019)

First report of Alternaria alternata causing postharvest fruit rot of peach in Pakistan - Muhammad Waqar Alam; Abdul Rehman; Aman Ullah Malik; Sidra Aslam; Mubeen Sarwar; Sajid Ali; Muhammad Arslan Khan; Akhtar Hameed; Sohaib Sarfraz (Journal of Plant Pathology, 2019)

Mapping sediment thickness of the Abbottabad basin, Pakistan - Zahid Hussain; Sarfraz Khan; Muhammad Asif Khan; Muhammad Waseem; Waqas Ahmed (Journal of Earth System Science, 2019)

Probabilistic seismic hazard assessment of Peshawar District, Pakistan - Ahmad Hammad Khaliq; Muhammad Waseem; Sarfraz Khan; Waqas Ahmed; Muhammad Asif Khan (Journal of Earth System Science, 2019)

The Small Matter of a Red Ox, a Particularly Sensitive Pink Cat, and the Quest for the Yellow Stone of Wisdom - Muhammad Jawad Nasim; Polina Denezhkin; Muhammad Sarfraz; Roman Leontiev; Yannik Ney; Ammar Kharma; Sharoon Griffin; Muhammad Irfan Masood; Claus Jacob (Current Pharmacology Reports, 2018)

Resistance in field populations of Amrasca devastans (Hemiptera: Cicadellidae) to new insecticides in Southern Punjab, Pakistan - Nasir Abbas; Naeem Abbas; Masood Ejaz; Sarfraz Ali Shad; Iqra Asghar; Aima Irum; Muhammad Binyameen (Phytoparasitica, 2018)

Assessment of field evolved resistance to some broad-spectrum insecticides in cotton jassid, Amrasca devastans from southern Punjab, Pakistan - Nasir Abbas; Muhammad Ismail; Masood Ejaz; Iqra Asghar; Aima Irum; Sarfraz Ali Shad; Muhammad Binyameen (Phytoparasitica, 2018)

Updated earthquake catalogue for seismic hazard analysis in Pakistan - Sarfraz Khan; Muhammad Waseem; Muhammad Asif Khan; Waqas Ahmed (Journal of Seismology, 2018)

Geology as a proxy for Vs30-based seismic site characterization, a case study of northern Pakistan - Muhammad Shafique; Mian Luqman Hussain; M. Asif Khan; Mark van der Meijde; Sarfraz Khan (Arabian Journal of Geosciences, 2018)

Impact of grazing on soil, vegetation and ewe production performances in a semi-arid rangeland - Muhammad Islam; Abdul Razzaq; Shamim Gul; Sarfraz Ahmad; Taj Muhammad; Sawsan Hassan; Barbara Rischkowsky; M. N. M. Ibrahim; Mounir Louhaichi (Journal of Mountain Science, 2018)

Assessing the combined toxicity of conventional and newer insecticides on the cotton mealybug Phenacoccus solenopsis - Bushra Saddiq; Masood Ejaz; Sarfraz Ali Shad; Muhammad Aslam (Ecotoxicology, 2017)

Retraction Note to: Estimation of Anticipated Performance Index and Air Pollution Tolerance Index and of vegetation around the marble industrial areas of Potwar region: bioindicators of plant pollution response - Mehwish Jamil Noor; Shazia Sultana; Sonia Fatima; Mushtaq Ahmad; Muhammad Zafar; Maliha Sarfraz; Masour A. Balkhyour; Sher Zaman Safi; Muhammad Aqeel Ashraf (Environmental Geochemistry and Health, 2017)

Seismic attributes’ application to evaluate the Goru clastics of Indus Basin, Pakistan - Muhammad Naseer Tayyab; Shazia Asim; Muhammad Mass Siddiqui; Muhammad Naeem; Sarfraz Hussain Solange; Farhan Khan Babar (Arabian Journal of Geosciences, 2017)

Studies on genetics, stability and possible mechanism of deltamethrin resistance in Phenacoccus solenopsis Tinsley (Homoptera: Pseudococcidae) from Pakistan - BUSHRA SADDIQ; MUHAMMAD BABAR SHAHZAD AFZAL; SARFRAZ ALI SHAD (Journal of Genetics, 2016)

RETRACTED ARTICLE: Floristic and ethnoecological diversity in various habitats of a semi-arid area in the Chakwal district (Pakistan), with special emphasis on medicinal plants - Mehwish Jamil Noor; Mushtaq Ahmad; Muhammad Zafar; Maliha Sarfraz; Ismail Yusoff; Yatimah Alias; Muhammad Aqeel Ashraf (Plant Ecology, 2016)

Resistance risk analysis to acetamiprid and other insecticides in Acetamiprid-Selected population of Phenacoccus solenopsis - Mamuna Ijaz; Muhammad Babar Shahzad Afzal; Sarfraz Ali Shad (Phytoparasitica, 2016)

Tissue specific metal characterization of selected fish species in Pakistan - Mukhtiar Ahmed; Taufiq Ahmad; Muhammad Liaquat; Kashif Sarfraz Abbasi; Ibrahim Bayoumi Abdel Farid; Muhammad Jahangir (Environmental Monitoring and Assessment, 2016)

Deltamethrin resistance in the cotton mealybug, Phenacoccus solenopsis Tinsley: Cross-resistance to other insecticides, fitness cost analysis and realized heritability - Bushra Saddiq; Naeem Abbas; Sarfraz Ali Shad; Muhammad Aslam; Muhammad Babar Shahzad Afzal (Phytoparasitica, 2016)

Genetics, realized heritability and preliminary mechanism of spinosad resistance in Phenacoccus solenopsis Tinsley (Homoptera: Pseudococcidae): an invasive pest from Pakistan - Muhammad Babar Shahzad Afzal; Sarfraz Ali Shad; Naeem Abbas (Genetica, 2015)

Baseline susceptibility and resistance stability of Earias vittella fabricius (Lepidoptera: Noctuidae) to cypermethrin, deltamethrin and spinosad - Muhammad Tahir Jan; Naeem Abbas; Sarfraz Ali Shad; Muhammad Rafiq; Mushtaq Ahmad Saleem (Phytoparasitica, 2015)

Tomato ( Solanum lycopersicum ) Carotenoids and Lycopenes Chemistry; Metabolism, Absorption, Nutrition, and Allied Health Claims—A Comprehensive Review - Rashida Perveen; Hafiz Ansar Rasul Suleria; Faqir Muhammad Anjum; Masood Sadiq Butt; Imran Pasha; Sarfraz Ahmad (Critical Reviews in Food Science and Nutrition, 2015)

RETRACTED ARTICLE: Estimation of Anticipated Performance Index and Air Pollution Tolerance Index and of vegetation around the marble industrial areas of Potwar region: bioindicators of plant pollution response - Mehwish Jamil Noor; Shazia Sultana; Sonia Fatima; Mushtaq Ahmad; Muhammad Zafar; Maliha Sarfraz; Masour A. Balkhyour; Sher Zaman Safi; Muhammad Aqeel Ashraf (Environmental Geochemistry and Health, 2015)

Effect of emamectin benzoate on life history traits and relative fitness of Spodoptera litura (Lepidoptera: Noctuidae) - Syed Muhammad Zaka; Naeem Abbas; Sarfraz Ali Shad; Rizwan Mustafa Shah (Phytoparasitica, 2014)

Increased fitness and realized heritability in emamectin benzoate-resistant Chrysoperla carnea (Neuroptera: Chrysopidae) - Muhammad Mudassir Mansoor; Naeem Abbas; Sarfraz Ali Shad; Attaullah Khan Pathan; Muhammad Razaq (Ecotoxicology, 2013)

Field evolved resistance to carbamates, organophosphates, pyrethroids, and new chemistry insecticides in Spodoptera litura Fab. (Lepidoptera: Noctuidae) - Sarfraz Ali Shad; Ali H. Sayyed; Sahar Fazal; Mushtaq A. Saleem; Syed Muhammad Zaka; Muhammad Ali (Journal of Pest Science, 2012)

Microcalorimetric Method to Assess Phagocytosis: Macrophage-Nanoparticle Interactions - M. H. D. Kamal Al-Hallak; Muhammad Khan Sarfraz; Shirzad Azarmi; M. H. Gilzad Kohan; Wilson H. Roa; Raimar Löbenberg (The AAPS Journal, 2011)

Bioremediation and Phytoremediation of Pesticides: Recent Advances - Sarfraz Hussain; Tariq Siddique; Muhammad Arshad; Muhammad Saleem (Critical Reviews in Environmental Science and Technology, 2009)

Concentration dependent growth/non-growth linked kinetics of endosulfan biodegradation by Pseudomonas aeruginosa - Sarfraz Hussain; Muhammad Arshad; Baby Shaharoona; Muhammad Saleem; Azeem Khalid (World Journal of Microbiology and Biotechnology, 2009)

Microbial transformation of 18β-glycyrrhetinic acid by Cunninghamella elegans and Fusarium lini , and lipoxygenase inhibitory activity of transformed products - Muhammad Iqbal Choudhary; Zafar Ali Siddiqui; Sarfraz Ahmed Nawaz; Atta-ur-Rahman (Natural Product Research, 2009)

Estimation of Toxic Metals in Scalp Hair Samples of Chronic Kidney Patients - Tasneem Gul Kazi; Nusrat Jalbani; Naveed Kazi; Muhammad Balal Arain; Muhammad Khan Jamali; Hassan Imran Afridi; Ghulam Abbas Kandhro; Raja Adil Sarfraz; Abdul Qadir Shah; Rehana Ansari (Biological Trace Element Research, 2009)

A pharmacological and toxicological evaluation of Haloxylon recurvum - Abdul Wahab; Ejaz Ahmed; Sarfraz Ahmad Nawaz; Ahsan Sharif; Rizwan Ul Haq; Abdul Malik; Muhammad Iqbal Choudhary; Mohsin Raza (Natural Product Research, 2008)

Biodegradation of α- and β-endosulfan by soil bacteria - Sarfraz Hussain; Muhammad Arshad; Muhammad Saleem; Azeem Khalid (Biodegradation, 2007)

Screening of soil fungi for in vitro degradation of endosulfan - Sarfraz Hussain; Muhammad Arshad; Muhammad Saleem; Zahir Ahmad Zahir (World Journal of Microbiology and Biotechnology, 2007)

The microbiological hydroxylation of levonorgestrel - Muhammad Iqbal Choudhary; Muhammad Atif Sarfraz; A. Nawaz; Muhammad Qaiser Fatmi; Atta-Ur-Rahman (Natural Product Research, 2006)

Phenolic constituents from Perovskia atriplicifolia - Shagufta Perveen; Sher Bahadar Khan; Abdul Malik; Rasool Bakhsh Tareen; Sarfraz Ahmad Nawaz; Muhammad Iqbal Choudhary (Natural Product Research, 2006)